Double-Sided Sliding-Paraboloid (DSSP): A new tool for preprocessing GPR data. (May 2017) - Rashed, Mohamed; Rashed, Essam A.
Abstract: Background noise in Ground Penetrating Radar (GPR) data is a nagging problem that degrades the quality of GPR images and increases their ambiguity. There are several methods adopting different strategies to remove background noise. In this study, we present the Double-Sided Sliding-Paraboloid (DSSP) as a new background removal technique. Experiments conducted on field GPR data show that the proposed DSSP technique has several advantages over existing background removal techniques. DSSP removes background noise more efficiently while preserving first arrivals and other strong horizontal reflections. Moreover, DSSP introduces no artifacts to GPR data and corrects data for DC-shift and wow noise. Graphical abstract: Highlights: We propose a novel method for background noise removal in GPR data. The proposed method, named DSSP, is an extension of the rolling ball algorithm. DSSP method has several advantages in removing the background noise. Field GPR data are used for evaluation and indicate image quality improvement.